O potencial da música como recurso motivador na aula de língua inglesa da rede pública - Kawachi, Claudia Jotto; Monteiro, Dirce Charara [UNESP] (My University, 2010)
The aim of this study was to verify the potential of music as a pedagogical resource in the English class of a public school. The results confirmed that it is possible to motivate students through the use of songs.
Keywords: Music; Motivation; Teaching an learning English; Música; Motivação; Inglês; Ensino-aprendizagem